Avian speciation and biodiversity in South-east Sulawesi, Indonesia: drivers of diversification - O'CONNELL, DARREN (Trinity College Dublin. School of Natural Sciences. Discipline of Zoology, 2019)
As biodiversity loss reaches critical levels, greater knowledge of its distribution is needed to concentrate conservation efforts. Biodiversity can be measured at several levels, with the species typically the unit used in conservation planning. Attempts to set accurate conservation priorities face a number of prominent challenges; 1. species distributions are often poorly known, particularly in the tropics where the rate of biodiversity loss is highest, 2. the number of currently described species is known to be a huge underestimate, with many cryptic species awaiting formal description, and 3. much remains unknown about the drivers of speciation, particularly what adaptations are associated with population divergence in the early stages of the process. In this thesis I explore each of these main topics in a study system in South-east Sulawesi, in the biodiversity hotspot of the Wallacea region. I focus on the avifauna of the region, contributing to characterising the community composition of unstudied islands, assess the species status of island populations which have diverged from the mainland and provide insight into how adaptations to island life may drive population divergence. In Chapters 2 and 3 we filled in some of the gaps in the knowledge of the avifaunal distribution in South-east Sulawesi on the previously unsurveyed islands of Kabaena, Muna and Wawonii, identifying potentially important populations, particularly for the Endangered Milky Stork Mycteria cinerea. Chapters 4 and 5 evaluated the diversification of the ‘great speciator’ taxa of South-east Sulawesi, Zosterops white-eyes and Todiramphus kingfishers, lineages renowned for their wide range and propensity for speciation. We propose two new white-eye species, an isolated population descended from the widespread island coloniser the Lemon-bellied White-eye Zosterops chloris, and a single island endemic the ‘Wangi-wangi White-eye’. The ‘Wangi-wangi White-eye’ is a particularly intriguing new species, as its closest relatives are found >3000 km away in the Solomon Islands. Chapters 4 and 5 also flag up other populations for further taxonomic refinement, the Wakatobi Islands Collared Kingfisher Todiramphus chloris population and Runduma Island Lemon-bellied White-eye populations may represent endemic subspecies for South-east Sulawesi. Chapters 4-7 investigated different morphological adaptations that are associated with island colonisation and the early stages of speciation. Chapter 5 suggested that a reduced dispersal ability, in comparison to source populations, may be a feature of populations of widespread island colonisers which become isolated. In Chapter 4 we discussed how potential differences in habitat, and associated increases in interspecific competition, may have driven a niche shift in Collared Kingfishers on the Wakatobi Islands. Chapter 6 outlined how Lemon-bellied White-eyes had a larger morphological niche volume and greater population density in allopatry from the Pale-bellied White-eye Zosterops consobrinorum, on both a small island and in urban areas. Reduced interspecific competition, and greater intraspecific competition in high density populations, likely led to the increase in niche volume seen in the Lemon-bellied White-eye populations. This chapter highlights the potential for urban areas to act as ecological islands for island colonising edge species in the Indo-Pacific. Chapter 7 looked at some of the effects of island colonisation on sexual dimorphism. Showed that Olive-backed Sunbirds Cinnyris jugularis on the small oceanic Wakatobi Islands showed greater sexual dimorphism and higher population density than those on the mainland and continental islands. There was no difference in the niche volume of males from Wakatobi and mainland populations, but females from the Wakatobi Islands had a smaller niche volume than those from the mainland. Potentially their niche volume has contracted to reduce intersexual competition in the high density populations of the Wakatobi Islands. This thesis illustrates how studying the populations of Indo-Pacific island colonisers, particularly the ‘great speciator’ lineages, provides the opportunity to contribute both taxonomic revision and insight into the early stages of speciation. Their rapid speed of evolutionary change, ability to colonise islands and the frequency with which they are found in secondary sympatry makes ‘great speciators’ ideal groups in which to study speciation. This work is given impetus by the looming biodiversity crisis that threatens not just Southeast Asia, but the whole world. Much biodiversity, and the evolutionary lessons it can teach us, faces extinction before being formally recognised.
APPROVED
Keywords: Speciation; Evolution; Competition; Niche; Taxonomy; Birds; Avian; Wallacea; Sulawesi; Indo-Pacific; Biogeography; Biodiversity